Розроблення та валідація методики визначення ступеня інкапсуляції цитохрому С у ліпосомах - Кацай, Олексій Григорович; Прохоров, Віталій Валентинович; Григор'єва, Ганна Савівна; Краснопольський, Юрій Михайлович (Національний фармацевтичний університет, 2016)
A strategic pathway in creating high-potent medical products is with targeted therapeutic systems that are based on nanoparticles of various structure. Such particles are capable of providing a targeted effect and an increase in bioavailability of the medical products. A special place among modern targeted drug delivery systems is held by liposomal nanoparticles which have apparent advantages over nanoparticles of an another type The problem number one for pharmacy lies in developing specific methods of control of nanosize drug delivery systems. This research is dedicated to the development and validation of a technique for determining encapsulation efficiency of cytochrome C in liposomes. The subject of research comprised the obtained liposomal form of cytochrome C, placebo emulsion, and cytochrome C solution. The research was conducted in compliance with the ICH and FDA requirements and recommendations in relation to the development of HPLC methods of control of liposomal preparations. A method has been developed to enable the determination of encapsulation efficiency of cytochrome C in liposomal preparations and to allow for identifying the composition of liposomal nanoparticles of cytochrome C. This HPLC method has been validated in terms of specificity, limit of detection, and robustness in compliance with the recommended criteria. The technique may find its application in quality control of liposomal form of cytochrome C and in control points manufacturing process.
Development and validation of the method for determination of encapsulation efficiency of cytochrome C in liposomes
Keywords: ліпосоми; наночастинки; інкапсуляція; валідація; цитохром С; фосфоліпіди; високоефективна рідинна хроматографія; liposomes; nanoparticle; encapsulation efficiency; validation; cytochrome C; phospholipids; HPLC